PHARMACEUTICAL TREATMENT EFFECTIVENESS IN PATIENTS WITH ISCHEMIC STROKE - N. P. Musina; O. M. Drapkina; V. T. Ivashkin (Российский кардиологический журнал)
Cardiac embolism, often associated with atrial fibrillation, plays an important role in stroke pathogenesis. Stroke prevention requires targeting all risk factors. The paper is focused on the role of atrial fibrillation in stroke development, as well as on the relative importance of various medication groups in secondary stroke prevention (the original study data). The pharmaceutical treatment of patients with ischemic stroke should be targeted at blood pressure reduction to the target levels (<130 and 80 mm Hg), with the medications decreasing the risk of secondary stroke most effectively (calcium antagonists, diuretics, ACE inhibitors). Anticoagulant (warfarin) therapy in patients with atrial fibrillation should be controlled by the international normalised ratio (target levels 2,0-3,0).